Tofu Product Diversification through Community Empowerment: Enhancing MSME Economic Value in Labuhan Ratu I Village, East Lampung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community-based empowerment program was conducted in Labuhan Ratu I Village, East Lampung, to enhance the economic value of tofu products through diversification for micro, small, and medium enterprises (MSME). The main problem identified was the limited product innovation of Barokah Tofu MSME and the underutilization of tofu waste, which posed environmental concerns. This study aimed to evaluate the effectiveness of participatory tofu product diversification training in improving community capacity and economic opportunities. The program applied a participatory action approach involving 28 participants consisting of MSME actors and PKK (Pemberdayaan dan Kesejahteraan Keluarga)  women. The activities included socialization, hands-on production training, and mentoring in packaging and simple digital marketing. Program effectiveness was measured using pre-test and post-test evaluations. The results showed a significant increase in participants’ knowledge, from 16% prior understanding to 100% post-training comprehension. The diversified product demonstrated improved shelf life and higher market potential compared to fresh tofu. Economically, the program increased value-added opportunities, while socially strengthening women’s entrepreneurial roles. Environmentally, tofu waste utilization supported sustainable production practices. These findings indicate that participatory food diversification training can serve as an effective community empowerment model to enhance rural MSME competitiveness and sustainability.